Strategi Manajemen Pengembangan Sumber Daya Manusia Dalam Meningkatkan Keunggulan Kompetitif Di Pondok Pesantren Baitul Abidin Kota Batu - Arif Irvan; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
Abstract Pesantren as an institution based on the quality of Islamic education, in practice can survive its existence which will continue to be viewed positively by the community. Pesantren currently has real local conditions that cannot keep up with the times. The regeneration factor of Human Resources (HR), which does not indicate the condition of pesantren, among them can be said that they are